Here is what I got the second time I tried (the first one was shorter):
To find the derivative of x^x, we can use logarithmic differentiation. Here are the steps:
1. Rewrite the expression using logarithms:
Start by taking the natural logarithm of both sides of the equation y==x^x:
ln(y)==ln(x^x)==xln(x)
2. **Differentiate both sides with respect to x:**
Using implicit differentiation, differentiate both sides:
d/(d x) [ln(y)]==d/(d x) [xln(x)]
The left side differentiates to:
1/y (d y)/(d x)
The right side, using the product rule, differentiates to:
ln(x)+x\[CenterDot]1/x==ln(x)+1
3. **Solve for (d y)/(d x):**
Multiply both sides by y to solve for the derivative:
(d y)/(d x)==y(ln(x)+1)
4. **Substitute back y==x^x:**
Finally, replace y with x^x to get the derivative in terms of x:
(d y)/(d x)==x^x (ln(x)+1)
So, the derivative of x^x is:
x^x(ln(x)+1)
This matches the result you have in your notebook. If you need any more help, feel free to ask!